2004
DOI: 10.1002/bit.20154
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsisglycosyltransferases as biocatalysts in fermentation for regioselective synthesis of diverse quercetin glucosides

Abstract: Regioselectivity of glycosyltransferases offers an important means to overcome the limitations of chemical synthesis of small molecule glycosides. In this study we explore a large multigene family of UDP-glucose:glycosyltransferases of Arabidopsis for their potential as novel biocatalysts for in vitro synthesis and whole-cell catalysis. We used quercetin as a substrate for this study because the flavonol and its glycosides have important medicinal properties and the metabolite provides a complex structure for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
190
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(197 citation statements)
references
References 38 publications
7
190
0
Order By: Relevance
“…Recently, there has been increasing interest in biocatalytic synthesis of glucosides of quercetin (27,37) and other phenolic compounds (38) due to their potential therapeutic value in cardiovascular disease and cancer, and their antimicrobial properties. Specific quercetin mono-or diglucosides have been successfully produced in an E. coli fermentation system employing regiospecific glycosyltransferases (27,37) The majority of the soluble glucoside products are secreted to the medium that facilitates their purification. We have now demonstrated that new glycosyltransferases with altered regioselectivity for quercetin can be obtained through targeted mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been increasing interest in biocatalytic synthesis of glucosides of quercetin (27,37) and other phenolic compounds (38) due to their potential therapeutic value in cardiovascular disease and cancer, and their antimicrobial properties. Specific quercetin mono-or diglucosides have been successfully produced in an E. coli fermentation system employing regiospecific glycosyltransferases (27,37) The majority of the soluble glucoside products are secreted to the medium that facilitates their purification. We have now demonstrated that new glycosyltransferases with altered regioselectivity for quercetin can be obtained through targeted mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Reactions were stopped with 5 l of trichloroacetic acid (240 mg/ml) and extracted with 250 l of ethyl acetate. The extracted residues were resuspended in methanol and analyzed by reverse-phase HPLC (Hewlett Packard 1100 system) on a The glycosylated products were determined according to their relative retention times (27), UV spectra, and comparison to authentic standards. For kinetic studies, reaction mixtures contained 50 mM Tris-HCl (pH 7.0), 14 mM 2-mercaptoethanol, 10 M UDP-[U-…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Notably, genes encoding enzymes involved in the synthesis of isoflavonoids, flavonols, and proanthocyanidins, which share metabolic precursors with anthocyanins, did not show changes in expression or were repressed, as in the case of the flavonol biosynthetic genes FLS2 (Owens et al, 2008;Guo et al, 2014), UGT78D1 (Jones et al, 2003), and UGT71D1 (Lim et al, 2004) (Supplemental Table S1). …”
Section: Expression Of a Repressor Form Of Tcp15 Causes An Increase Imentioning
confidence: 99%
“…The amino acid sequence of PaGT3 is homologous to that of flavonol 3-O-glucosyltransferase from A. thaliana (identity 56%) [25] and Fragaria x ananassa (identity 57%) [26], anthocyanin 3'-O-glucosyltransferase from Gentiana triflora (identity 56%) [27], and flavonol 7-O-glucosyltransferase from A. thaliana (identity 54%) [25]. Sequence identity between PaGT3 and PaGT2 is 27%, and PaGT2 is related to hydroquinone glucosyltransferase from Rauvolfia serpentine (identity 58%) [28] and coniferyl alcohol 4-O-glucosyltransferase from A. thaliana (identity 39%) [29].…”
Section: Introductionmentioning
confidence: 99%